ELASTIC SLIP MODEL IN ‘WHEEL — ROAD SURFACE’ SYSTEM - Mikhail Victorovich Chuveyko; Sergey Victorovich Nosachev (Advanced Engineering Research, 2013)
A mathematical model of the wheel — road surface interaction is presented. This model permits to carry out a qualitative investigation on the wheel swing specificity in a coupling case. The experimental investigation is implemented through the numerical modeling methods. In the obtained mathematical model, it is assumed that the inflexibility of the road is rather great, and its deformations can be neglected. The surface of the wheel is specified by a set of points. The research results have shown a lack of the trivial dependence between the angular frequency of the wheel and the linear speed of its centre. It was established that the linear speed of the wheel movement depends considerably on the value of the external loading. The work results are of interest in the mechanical engineering problems, in particular — in the construction of the exact positioning systems.